Claiming Space: Structural aspects of heterophony in the Vietnamese tradition of Vọng Cổ Performance - Nguyễn, Thanh; Östersjö, Stefan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
This paper seeks to better understand the role of heterophony in a form of traditional Vietnamese music often referred to as Đờn Ca Tài Tử, as well as how such performance practices are grounded in interactions between performers. The performance of this genre is analyzed as ornamental heterophony and attention is given to the role of idiomatic patterns as well as small-scale ornamentation. Building on stimulated recall interviews with three master performers, the authors analyze an audio recording of Vọng Cổ by these three performers, in order to explore the role of conscious and subconscious processes in their performance.